Integrating FIB-4 and APRI into Clinical Practice Guidelines: A Literature Review - Ghaniyya, Willandra Fitriyanri; Humairah , Ira; Kholili , Ulfa (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
The FIB-4 and APRI indices have emerged as pivotal tools in the non-invasive assessment of liver fibrosis and cirrhosis, providing clinicians with accessible and cost-effective alternatives to liver biopsy. These scoring systems utilize routine laboratory parameters to stratify patients based on their risk of advanced fibrosis, making them especially valuable in managing chronic hepatitis B (HBV), hepatitis C (HCV), and non-alcoholic fatty liver disease (NAFLD). Their integration into clinical practice has significantly improved diagnostic accuracy and reduced the burden of invasive procedures, particularly in resource-constrained settings. Despite their advantages, the global adoption of FIB-4 and APRI faces several barriers. Variability in healthcare infrastructure, access to diagnostic resources, and differences in patient populations pose challenges to their consistent implementation. Furthermore, inequality in healthcare delivery systems and a lack of standardized protocols can lead to inconsistent utilization, particularly in low- to middle-income countries. Addressing these obstacles is critical to ensuring equitable and reliable liver disease assessment across diverse healthcare systems. Future research should focus on refining these indices, exploring their performance in diverse populations, and integrating them with emerging diagnostic technologies. Policymakers and healthcare stakeholders must work collaboratively to develop adaptable clinical guidelines that incorporate non-invasive liver tests into routine practice. By overcoming these challenges, the global integration of FIB-4 and APRI has the potential to transform liver disease management, improve patient outcomes, and promote health equity worldwide.